Pengembangan Puzzle Berbasis Make A Match Materi IPA Daur Hidup Mahluk Hidup Kelas IV SD - Siwi Purwanti; Khusnul Khotimah (Universitas Sarjanawiyata Tamansiswa, 2020)
Media is a very effective tool used for learning. This research is motivated by the lack of learning media in schools. This study aims to determine the steps of media development, media quality by experts, teachers and students. This research is a type of research and development (R&D) ADDIE development methods, namely analysis, design, development, implementation and evaluation. Data collection techniques using expert validation sheets, student assessment sheets and teacher assessment sheets are then analyzed using qualitative and quantitative data.The results of this study indicate that research and development has been carried out with the ADDIE step, the results of the study showed that the development of puzzle media based on make a match material for the life cycle of living creatures in fourth grade elementary school was declared feasible and received positive responses from students and teachers. The results of the validation produced by media experts got a value of 98 in the excellent category. the value resulting from the validation of the material experts obtained 85.3 in good category and the validation results produced by learning experts obtained 84 grades in good categories. With the final average overall results obtained 92.5 with a very good category.